2011
DOI: 10.1371/journal.pone.0029375
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Model of Cellular Mechanisms of Temporal Coding in the Medial Geniculate Body (MGB)

Abstract: Acoustic stimuli are often represented in the early auditory pathway as patterns of neural activity synchronized to time-varying features. This phase-locking predominates until the level of the medial geniculate body (MGB), where previous studies have identified two main, largely segregated response types: Stimulus-synchronized responses faithfully preserve the temporal coding from its afferent inputs, and Non-synchronized responses, which are not phase locked to the inputs, represent changes in temporal modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 70 publications
1
21
0
Order By: Relevance
“…This indicates that response jitter can limit the range of sound shapes to which a neuron or cortical field may respond. In addition, models of neural spiking suggest that an increase in response duration and jitter should limit response synchronization and the capacity to temporally encode sound modulation frequency (Escabí and Read 2003;Lu and Wang 2004;Rabang and Bartlett 2011). Accordingly, we found the proportion of response power with synchronized spiking (i.e., the maximum temporal coding fraction) decreased almost twofold between A1 and cSRAF (e.g., Fig.…”
Section: Spike-timing Changes With Temporal Sound Cues In Primary Andmentioning
confidence: 57%
“…This indicates that response jitter can limit the range of sound shapes to which a neuron or cortical field may respond. In addition, models of neural spiking suggest that an increase in response duration and jitter should limit response synchronization and the capacity to temporally encode sound modulation frequency (Escabí and Read 2003;Lu and Wang 2004;Rabang and Bartlett 2011). Accordingly, we found the proportion of response power with synchronized spiking (i.e., the maximum temporal coding fraction) decreased almost twofold between A1 and cSRAF (e.g., Fig.…”
Section: Spike-timing Changes With Temporal Sound Cues In Primary Andmentioning
confidence: 57%
“…Studies in unanesthetized marmoset show that MGB neurons display increasingly complex response properties to modulated sounds and click stimuli (Bartlett and Wang, 2007, 2011, Rabang and Bartlett, 2011). Wallace et al (2000, 2002, 2007) examined responses to modulated pure-tone and click stimuli in these three auditory structures and found increased complexity in coding as one ascended the auditory neuraxis.…”
Section: Discussionmentioning
confidence: 99%
“…A rate code transformation for modulated signals has been extensively described for the MGB (Bartlett and Wang, 2007, 2011, Rabang and Bartlett, 2011). We previously reported that the MGB units showed a dose-dependent, enhanced sensitivity to GABA application relative to units in the IC (Cai et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations